Angle of attack of center of mass during the running of an entire 100 m dash - Rodrigues, N. de A.; Monezi, L. A.; Mercadante, L. A.; Misuta, M. S. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The angle of attack is related to the body posture and changes during sprinting because of changes in the horizontal velocity. The aim of this study was to analyze the angle of attack of the center of mass and the horizontal velocity during a 100 m dash. Twelve video cameras were positioned along a running track to obtain the position of the center of mass. The horizontal velocity was derived from the position data. When the different sides were compared, the angles were lower on the right side than on the left side (P < 0.05), which tended to decrease with increasing horizontal velocity. The results show the variability of the angle of attack as associated to the horizontal velocity, and the differences considering laterality.